Global trends of da’wah research in the digital era: Scopus-based bibliometric analysis - Raih Rohania Hidayat; Heru Wibowo (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2026)
The development of digital technology has transformed Islamic da’wah practices and strategies globally. Although digital da’wah has become integral to socio-religious life, scientific studies mapping global trends remain limited, particularly those based on quantitative data from reputable sources like Scopus. This study analyzes global trends in digital da’wah research using a bibliometric approach, drawing on 170 journal articles published between 2013 and 2025 and indexed in Scopus. The bibliometric method evaluates publication patterns, prolific authors, international collaborations, topic evolution, and keyword networks. Results show a sharp increase in publications since 2019, peaking in 2024. Topics such as Islam, social media, and digital religion dominate as motor themes, while Islamic education and digital literacy show potential as future trends. Indonesia contributes the most publications, though international collaboration remains limited. This study's novelty lies in the comprehensive global mapping of digital da’wah trends using Scopus bibliometric data, an approach that has rarely been used before. The main contribution is to present a conceptual framework that connects the digital era, da’wah media, and Islamic social transformation, and to provide insights to help academics and practitioners design more adaptive, data-driven da’wah strategies in the digital age.